Inovasi Pelayanan Administrasi Kependudukan Melalui Anjungan Dukcapil Mandiri: (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Magetan) - Wincahyo Artiko Aji, Nawangsasi; Supriyono, Bambang; Shobaruddin, Muhammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
The population and Civil Registration Agency of Magetan Regency met a variety of unresolved issues in the population administration service process, including centralized service sites, restricted queue numbers, long queues, and the rise of the broker phenomenon. The Anjungan Dukcapil Mandiri (ADM) machine is employed as a solution, making it the first local government in Indonesia to take action. Even though it has been demonstrated that it can solve a variety of issues, the adoption of these technologies in Indonesia is still quite restricted. The goal of this research is to determine how the process of utilizing the ADM machine in Magetan Regency from the beginning of planning to its stability, as well as the supporting and inhibiting variables, so that the successful use of the ADM machine in Magetan Regency may be copied by other local governments. The research approach employed is qualitative research utilizing narrative methodologies. The study's findings indicate that Magetan Regency started preparing for the ADM machine as long as it was implemented. In 2023, the Magetan Regency Dispendukcapil has three ADM machines located at the Public Service Mall, the Barat District Office, and the Kawedanan District Office.